Efeitos não-alvo de inseticidas utilizados para controle de Bemisia tabaci (Gennadius, 1889) biótipo B (Hemiptera: Aleyrodidae) sobre a mortalidade e biologia de Spodoptera frugiperda (Smith, 1797) (Lepidoptera: Noctuidae) em soja [Glycine max (l.) Merrill] - Santana, Lucas S.; Vilhasanti, Camila B.; Degrande, Paulo E.; Souza, Ellen P.; Scoton, Ana M. N.; Pereira, Matheus D. C. (Entomological Communications, 2023)
Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) is a polyphagous pest that has gained importance in soybean cultivation in recent years, due to the damage it causes to leaves and pods. The objective of this work was to evaluate the non-target effect of insecticides recommended and used to control Bemisia tabaci (Genn.) biotype B on S. frugiperda. The experimental design was entirely randomized with five treatments and fifty replications. The treatments were: 1. negative control (distilled water), 2. positive control (lufenuron), 3. buprofezin, 4. pyriproxyfen, and 5. diafenthiuron. In each replicate, one caterpillar was placed in a plastic cup, where sprayed soybean leaves with the maximum dosage of insecticides recommended for B. tabaci were placed.The treatments were evaluated daily during all stages: larval, pupal, and adult emergence and fecundity. The results obtained for larval mortality showed that diafenthiuron aimed 100% control, followed by pyriproxyfen with 28% and buprofezin with 12%. The duration of the larval period of the insects exposed to pyriproxyfen and buprofezin were longer compared to the control. While the biological parameters of pupae were found that pyriproxyfen caused lower pupal formation rate and higher pupal mortality, followed by buprofezin. In adult emergence, pyriproxyfen showed the lowest rate with 13.8% and the highest percentage of deformed adults with 60%. Thus, it was possible to conclude that the insecticides under study cause S. frugiperda mortality or effects on its biological patterns.